2021
DOI: 10.3389/fpls.2021.746586
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Detection and Quantification of Plant Innate Immunity Response Using Raman Spectroscopy

Abstract: We have developed a rapid Raman spectroscopy-based method for the detection and quantification of early innate immunity responses in Arabidopsis and Choy Sum plants. Arabidopsis plants challenged with flg22 and elf18 elicitors could be differentiated from mock-treated plants by their Raman spectral fingerprints. From the difference Raman spectrum and the value of p at each Raman shift, we derived the Elicitor Response Index (ERI) as a quantitative measure of the response whereby a higher ERI value indicates a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…However, the field of portable Raman for agricultural applications is rapidly advancing, adding merits of miniaturization, lower costs, and shorter spectrum acquisition time (47)(48)(49). As an example, handheld Raman spectrometers were recently developed for nondestructive monitoring of plant stresses in the field (50)(51)(52). As for verification of the visual PUF tags, the pocket microscope used in this study currently costs less than 23 USD, is battery-powered, and weighs less than 230 g. With a resolution of 1920 × 1080 pixels, the pocket microscope can be conveniently connected to a smartphone via its built-in Wi-Fi function so that anyone with a smartphone will be able to scan the visual tags and save the captured tag images in their smartphone or on a cloud service within seconds.…”
Section: Discussionmentioning
confidence: 99%
“…However, the field of portable Raman for agricultural applications is rapidly advancing, adding merits of miniaturization, lower costs, and shorter spectrum acquisition time (47)(48)(49). As an example, handheld Raman spectrometers were recently developed for nondestructive monitoring of plant stresses in the field (50)(51)(52). As for verification of the visual PUF tags, the pocket microscope used in this study currently costs less than 23 USD, is battery-powered, and weighs less than 230 g. With a resolution of 1920 × 1080 pixels, the pocket microscope can be conveniently connected to a smartphone via its built-in Wi-Fi function so that anyone with a smartphone will be able to scan the visual tags and save the captured tag images in their smartphone or on a cloud service within seconds.…”
Section: Discussionmentioning
confidence: 99%
“…They demonstrated that Raman spectral fingerprints could be used to distinguish between infected and noninfected plants, by employing flg22 and elf18 elicitors. The difference between the p value at each Raman shift was used to derive the elicitor response index (ERI) to quantify the immune response . Charlermroj et al reported a method involving use of immunoassay technology to detect four plant pathogens, out of which three were viruses and one was a bacterium.…”
Section: Recent Protein-based Approach For Plant Pathogen Detectionmentioning
confidence: 99%